Evaluating treatment options for symptomatic uterine fibroids: a systematic review and meta-analysis of effectiveness, recovery, and long-term outcomes (MARIE WP1) - Bedggood, Elena; Jie, Sun; Ghosh, Snehal; Pathiraja, Vindya; Mudalige, Tharanga; Rathnayake, Nirmala; Cavalini, Heitor; Kurmi, Om; Eleje, George Uchenna; Phiri, Peter; Briggs, Paula; Shi, Jian Qing; et al. (Frontiers in Global Women's Health, 2025)
BackgroundUterine fibroids can significantly impair the quality of life of women. While most fibroids remain asymptomatic, 25% of women diagnosed with uterine fibroids require medical intervention.MethodsA systematic review and meta-analysis protocol was developed and published in PROSPERO (CRD42022346251) to explore surgical treatment outcomes linked to uterine fibroids. Data was gathered using PubMed, Web of Science and ScienceDirect. The pooled data was analysed using the meta-package (version 8.0–1 and version 4.6–0) in R software (version 4.4.2).ResultsFive studies met the eligibility criteria, and were further analysed to report quality of life, symptom severity and complications linked to surgery. Three studies (n = 520) assessed HRQoL via UFS-QoL pre- and post-uterine artery embolisation and myomectomy. The pooled mean difference was −6.99 [95% CI: (−16.49, 2.51); I2 = 71.9%; P = 0.03], indicating no significant difference in quality of life impact between procedures. However, the pooled mean difference for UFS-QoL symptom severity was 4.85 [95% CI: (0.50, 9.21); I2 = 0.0%; P = 0.52], suggesting myomectomy significantly reduces symptom severity compared to uterine artery embolisation. Most studies did not report race and ethnicity, and the study sample was not representative of the global female populous.ConclusionUterine artery embolisation and myomectomy result in comparable improvements in health-related quality of life although myomectomy appears to offer a greater reduction in symptom severity compared to uterine artery embolisation. These findings can assist clinicians and patients make improved shared decisions when selecting the most appropriate treatment for uterine fibroids. Improved research study designs and representation in sample need to be considered when conducting future research.